Reservoir formation damage fundamentals, modeling, assessment, and mitigation - Civan, Faruk (Amsterdam ; Boston : Gulf Professional Pub., 2007)
Reservoir Formation Damage, Second edition is a comprehensive treatise of the theory and modeling of common formation damage problems and is an important guide for research and development, laboratory testing for diagnosis and effective treatment, and tailor-fit- design of optimal strategies for mitigation of reservoir formation damage. The new edition includes field case histories and simulated scenarios demonstrating the consequences of formation damage in petroleum reservoirs Faruk Civan, Ph. D., is an Alumni Chair Professor in the Mewbourne School of Petroleum and Geological Engineering at the University of Oklahoma in Norman. Dr. Civan has received numerous honors and awards, including five distinguished lectureship awards and the 2003 SPE Distinguished Achievement Award for Petroleum Engineering Faculty. *Petroleum engineers and managers get critical material on evaluation, prevention, and remediation of formation damage which can save or cost millions in profits from a mechanistic point of view. *State-of-the-Art knowledge and valuable insights into the nature of processes and operational practices causing formation damage *Provides new strategies designed to minimize the impact of and avoid formation damage in petroleum reservoirs with the newest drilling, monitoring, and detection techniques.
Preface -- Chapter 1Overview of Formation Damage -- PART I -- Characterization of Reservoir Rock for Formation Damage Mineralogy, Texture, Petrographics, Petrophysics, and Instrumental Techniques -- Chapter 2 Mineralogy and Mineral Sensitivity of PetroleumBearing Formations -- Chapter 3 Petrographical Characteristics of Petroleum-Bearing Formations -- Chapter 4 PetrophysicsFlow Functions and Parameters -- Chapter 5 Porosity and Permeability Relationships of Geological Formations -- Chapter 6 Instrumental and Laboratory Techniques for Characterization of Reservoir Rock -- PART II -- Characterization of the Porous Media Processes for Formation DamageAccountability of Phases and Species, Rock-Fluid-Particle Interactions, and Rate Processes -- Chapter 7 Multi-Phase and Multi-Species Transport in Porous Media -- Chapter 8Particulate Processes in Porous Media -- Chapter 9Crystal Growth and Scale Formation in Porous Media -- PART III -- Formation Damage by Particulate Processes -- Chapter 10Single-Phase Formation Damage by Fines Migration and Clay Swelling -- Chapter 11 Multi-Phase Formation Damage by Fines Migration -- Chapter 12Cake Filtration: Mechanism, Parameters and Modeling -- PART IV -- Formation Damage by Inorganic and Organic ProcessesChemical Reactions, Saturation Phenomena, Deposition, and Dissolution -- Chapter 13Inorganic Scaling and Geochemical Formation Damage -- Chapter 14Formation Damage by Organic Deposition -- PART V -- Assessment of the Formation Damage PotentialTesting, Simulation, Analysis, and Interpretation -- Chapter 15Laboratory Evaluation of Formation Damage -- Chapter 16 Formation Damage Simulator Development -- Chapter 17 Model Assisted Analysis and Interpretation of Laboratory and Field Tests -- PART VI -- Formation Damage Models for Fields Applications- Drilling Mud Invasion, Injectivity of Wells, Sanding and Gravel-Pack Damage, and Inorganic and Organic Deposition -- Chapter 18 Drilling Mud Filtrate and Solids Invasion and Mudcake Formation -- Chapter 19Injectivity of the Waterflooding Wells -- Chapter 20 Reservoir Sand Migration and Gravel-Pack Damage: Stress-Induced Formation Damage, Sanding Tendency, and Prediction -- Chapter 21 Near-Wellbore Formation Damage by Inorganic and Organic Precipitates Deposition -- PART VII -- Diagnosis and Mitigation of Formation DamageMeasurement, Assessment, Control, and Remediation -- Chapter 22 Field Diagnosis and Measurement of Formation Damage -- Chapter 23Determination of Formation- and Pseudo-Damage from Well Performance- Identification, Characterization, and Evaluation -- Chapter 24Formation Damage Control and Remediation- Fundamentals -- Chapter 25Reservoir Formation Damage Abatement- Guidelines, Methodology, Preventive Maintenance, and Remediation Treatments -- Index.
Includes bibliographical references (p. 1028-1089) and index.
Keywords: Hydrocarbon reservoirs; Petroleum -- Geology; Electronic books